2023
DOI: 10.1002/smll.202206154
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Fullerene for Inhibition of SARS‐CoV‐2 Variants

Abstract: As virus outbreaks continue to pose a challenge, a nonspecific viral inhibitor can provide significant benefits, especially against respiratory viruses. Polyglycerol sulfates recently emerge as promising agents that mediate interactions between cells and viruses through electrostatics, leading to virus inhibition. Similarly, hydrophobic C60 fullerene can prevent virus infection via interactions with hydrophobic cavities of surface proteins. Here, two strategies are combined to inhibit infection of SARS‐CoV‐2 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…The helicities continuously improved to 100% (for L 60 -G-POB and L 102 -G-POB) with increase of MWs, consistent with the previous findings. 45 However, sulfated glycopolypeptides L (36,60,102) -SG-POB showed lower helicities compared to L (36,60,102) -G-POB due to the introduction of ion groups (Figure 2c). It has been demonstrated that the electrostatic interaction between ion groups (sulfonic acid groups) and water could disrupted the α-helical conformations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The helicities continuously improved to 100% (for L 60 -G-POB and L 102 -G-POB) with increase of MWs, consistent with the previous findings. 45 However, sulfated glycopolypeptides L (36,60,102) -SG-POB showed lower helicities compared to L (36,60,102) -G-POB due to the introduction of ion groups (Figure 2c). It has been demonstrated that the electrostatic interaction between ion groups (sulfonic acid groups) and water could disrupted the α-helical conformations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The optimized dose for L 60 -SG-POB was determined by evaluating the virus inhibition efficiency under different concentrations. The results indicated that the half-inhibitory concentration (IC 50 ) of L 60 -SG-POB was 0.71 μg/mL, which was much lower than the reported cases , (Figure a). Since the maximum inhibition efficiency was obtained at 3 μg/mL, the following experiments were carried out under the mass concentration of 3 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…In this following section, we first describe the stages of employing systematic literature review protocols for selecting and evaluating the metadata related to nanotechnology and materials in environmental and human protection. As it is previously described, the procedures of collecting data were conducted based on PRISMA 2020 protocols which was written by Page et al [ 10 ]. PRISMA 2020 protocols is the basic theoretical foundation for developing a good systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…Functionalized fullerenes, therefore, have utility in a range of applications including, but not limited to, photocatalysis, electrocatalysis, polymer solar cells, photovoltaics, environmental remediation, and pharmaceuticals. [29][30][31][32][33][34] Fullerenes are generally functionalized via "bottom-up" and "topdown" methodologies, together with synthetic processes and anchoring of motifs. Manipulation of fullerenes via supramolecular self-assembly and functionalization, grafting, doping with metallic and non-metallic heteroatoms, polymer coatings, noncovalent modification of 2D materials and nano-attachment reportedly enables precise regulation of material surface and overall characteristics.…”
Section: And Derivativesmentioning
confidence: 99%